POLA SUKU KATA BAHASA LISABATA [Lisabata Syllabe Pattern Language] - Erniati Erniati (TOTOBUANG, 2017)
The language of Lisabata is used as the first language by native speakers of the Lisabata community on Seram Island, Maluku, precisely in the border area of West Seram and East Seram, West Lisabata Village, Nualiali Village, Desa Sukaraja, and Kawa Village. SIL (2006: 16—17) identified this language as the dialect of dialect, the dialect of the Eastern Lisabata, Nuniani, Sukaraja, and Kawa, Austronesian classes. Until now, the language of Lisabata has  still been used as an oral communication tool by certain circles in life community speakers. Nevertheless, the language of Lisabata can be categorized as an almost extinct local language, since there has no inheritance process to the younger generation. To prevent this, it is necessary to make a variety of rescue efforts that one of them through research. This research provided an overview of the pattern of the Lisabata language syllables. This study aimed to describe the pattern of the Lisabata syllable, the Eastern Lisabata dialect. The method used  descriptive qualitative method. Data was obtained from the direct speech of the native speakers of the language and speakers who were considered capable. The results showed that the Lisabata syllabic pattern consists of V, VK, KV,  KVK, VKV, KKVK, , 1 / 2KV.Bahasa Lisabata dipakai sebagai bahasa pertama oleh penutur asli masyarakat Lisabata di Pulau Seram, Maluku, tepatnya di daerah perbatasan Seram Barat dan Seram Timur, Desa Lisabata Barat,  Desa Nualiali, Desa Sukaraja,  dan Desa Kawa. SIL (2006:16—17) mengidentifikasi bahasa ini sebagai bahasa dengan tempat dialeknya, yaitu dialek Lisabata Timur, Nuniani, Sukaraja, dan Kawa, kelas Austronesia. Hingga saaat ini, bahasa Lisabata masih digunakan sebagai alat komunikasi secara lisan oleh kalangan tertentu dalam kehidupan masyarakat penuturnya. Meskipun demikian, bahasa Lisabata dapat dikategorikan sebagai bahasa daerah yang hampir punah, karena tidak ada proses pewarisan kepada generasi mudanya.  Untuk mencegah hal tersebut, perlu dilakukan berbagai upaya penyelamatan yang salah satu diantaranya melalui penelitian. Penelitian ini memberikan gambaran tentang pola suku kata bahasa Lisabata. Penelitian ini bertujuan untuk mendiskripsikan pola suku kata bahasa Lisabata, dialek Lisabata Timur. Metode yang digunakan adalah meode kualitatif deskriptif. Data diperoleh dari ucapan langsung penutur asli bahasa tersebut dan penutur yang dianggap mampu. Hasil analisis menunjukkan bahwa pola suku kata bahasa Lisabata terdiri atas V,VK, KV, KVK, VKV, KKVK, 1/2KV,.